2017
DOI: 10.5812/ijem.40614
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of n-3 Polyunsaturated Fatty Acids Supplementation on Serum Irisin in Patients with Type 2 Diabetes: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: BackgroundDiabetes refers to a group of metabolic diseases with blood glucose of higher than normal ranges. Furthermore, n-3 polyunsaturated fatty acids are necessary for the regulation of the activity of human function. The effect of n-3 PUFA on diabetes has been investigated in animal studies, yet, the exact amount has not been set, to date. Irisin, as a new myokine, is released from skeletal muscle and Irisin levels decrease as a result of physical inactivity, overweightness, and obesity. Also, the reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The RCT included 43 patients with type 2 diabetes (21 patients in the placebo group and 22 patients in the omega-3 PUFA group) [ 40 ]. They were randomized to groups, one receiving 10 weeks of either omega-3 PUFA supplement and the other the placebo (1,250 mg capsule, three times per day).…”
Section: Resultsmentioning
confidence: 99%
“…The RCT included 43 patients with type 2 diabetes (21 patients in the placebo group and 22 patients in the omega-3 PUFA group) [ 40 ]. They were randomized to groups, one receiving 10 weeks of either omega-3 PUFA supplement and the other the placebo (1,250 mg capsule, three times per day).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that treatment with n-3 PUFA for 48 h will significantly increase irisin expression in human rhabdomyosarcoma cells. Furthermore, two recent randomized clinical trials discovered that n-3 PUFA supplementation, compared with placebo, can elevate the circulating irisin levels in patients with diabetic or coronary artery disease 53,54 . Combining the aforementioned two studies and the findings of the present study, we found that n-3 PUFA not only increases the level of circulating irisin, but also enhances the positive association between irisin and insulin sensitivity, which indicates that dietary n-3 PUFA intake might improve insulin sensitivity through irisin pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a plausible mechanism accounting for reduced IMCL accumulation in SkM PKCKO mice. Furthermore, adipokines such as adiponectin (7,8), myokines such as irisin and myonectin (1,14,27,47), and circulating factors produced by multiples cells types (i.e., interleukin-6, TNF-␣, and brain-derived neurotropic factor) (10,11,35) have the potential to orchestrate cross talk among skeletal muscle, adipose tissue, brain, liver, and pancreas in the regulation of metabolism and energy balance. A mechanistic link between alterations in skeletal muscle skeletal muscle metabolism, energy balance, and the plethora of circulating factors that may be involved requires further investigation.…”
Section: Discussionmentioning
confidence: 99%